Advanced lignin-derived hard carbon for Na-ion batteries and a comparison with Li and K ion storage. (February 2020) - Lin, Xiuyi; Liu, Yizhe; Tan, Hong; Zhang, Biao
Abstract: Hard carbon is the most attractive anode in Na-ion batteries. The performance of hard carbon relies primarily on the precursors and the synthesis approaches. Lignin, as the second-abundant biopolymer in nature, with the low cost and high carbon yield makes it an ideal precursor for the preparation of hard carbon. However, lignin-derived hard carbon from direct carbonization shows poor electrochemical performance. A low-temperature pre-oxidation is applied in this study to introduce carbonyl groups for enhancing the crosslink of lignin. Consequently, the growth and orientation of graphitic layers during carbonization are inhibited, which in turn increases the layer distance for facilitating the Na ion insertion and leads to exceptional rate capability and superb cyclic life. To gain insights into the charge storage mechanism, a comparison with Li- and K-ion storage in hard carbon is conducted through in-situ Raman tests. There are similarities of alkali-metal ion storage at high voltages but remarkable disparities at low voltages, thus emphasizing the importance of microstructure design of hard carbon depending on the application in various metal-ion batteries. Graphical abstract: Image 1